Large-aperture mesoporous silica nano-vesicle and preparation method thereof
By using a combination of nonionic surfactant and benzyl alcohol, large pore mesoporous silica nanovesicles were prepared, which solved the agglomeration and heterophase problems, and achieved the preparation of nanovesicles with good dispersion, which promoted the Development of the field.
Patent Information
- Application Number
- CN202411139286.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-20
- Publication Date
- 2024-12-20
AI Technical Summary
The prior art has agglomeration and heterophasic problems in the preparation of large-pore mesoporous silica nanovesicles, and the research on using nonionic surfactants as a single template agent is relatively lacking, resulting in slow development in this field.
Using nonionic surfactant as a single template agent, combined with benzyl alcohol as a co-solvent and boric acid as a catalyst, large pore mesoporous silica nanovesicles were prepared through hydrothermal reaction, and the reaction conditions and molar ratio were controlled to achieve good dispersion. , products without miscellaneous phases.
Successfully prepared mesoporous silica nanovesicles with large pore size and dispersion, which solved the agglomeration and heterophasic problems, provided a simple and controllable synthetic system, which is of great significance to the nanovesicles. Design and development of inorganic carriers.
Smart Images

Figure CN119160902A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nanocapsules, and in particular to a large-pore mesoporous silica nanocapsule and a preparation method thereof. Background Art
[0002] At present, the research on large-pore mesoporous silica nanovesicles (MSVs) has developed slowly due to the limitation of the synthesis system. The main synthesis methods include composite template method, single template method and special template method.
[0003] The composite template method is the most commonly used method for preparing MSVs, which mainly uses nonionic surfactants or cationic surfactants in combination with other template agents. Zhu et al. used P123 and hexane as composite template agents to synthesize MSVs with dual-mode structure for the first time. Li et al. used P123 and fluorocarbon surfactant (FC-4) in combination, and used n-butanol as an additive to successfully synthesize MSVs with a particle size of 50 to 300 nm. Subsequently, researchers only used the P123 / FC-4 system without using additives and successfully prepared MSVs with good dispersion. Sun et al. used long-chain alkanes (heptane or dodecane) in combination with P123 to successfully synthesize silica materials such as mesoporous nanofibers, multilayer vesicles and mesoporous foams. Other nonionic surfactants (P103) and sodium dodecyl sulfate (SDS) can also be used in combination to prepare MSVs with multilayer vesicle structure, and by changing the molar ratio of the template agent, the particle size of the final product and the cavity diameter of the vesicle can be controlled. MSVs can also be synthesized by using cationic surfactants in combination with other surfactants, such as sodium bis(2-ethylhexyl)sulfosuccinate (AOT), but the pore size of the final product synthesized by this method is small (2-7nm) and the particle size is large (200-1200nm). It is worth noting that the pore size of MSVs prepared by the hexadecyltrimethylammonium bromide (CTAB) composite template system is small (<5nm), which is not conducive to its loading of large molecular weight guest molecules. Most MSVs prepared by the composite template system of non-ionic surfactants have problems such as heterogeneity, agglomeration, and the need for fine control of the synthesis components. Some reaction systems also require the use of special template agents.
[0004] Compared with the composite template method, the single template method is simpler and less expensive to prepare MSVs. When the anionic surfactant N-lauroyl sarcosine sodium (Sar-Na) is used as a template, MSVs with a pore size of 4 to 9.6 nm can be successfully prepared, but its particle size is 3.2 mm; using CTAB as a surfactant and ether as an auxiliary reagent, MSVs with a pore size of 80 to 460 nm can be synthesized, and by increasing the concentration of ether, MSVs with different morphologies (snail-shaped, star-shaped, and bowl-shaped) can be synthesized; when sodium polyacrylate is used as a template, MSVs with a shell thickness of 4 to 20 nm and a particle size of 100 to 300 nm can be synthesized; using dodecyl dimethyl ammonium bromide (DDAB) with low kinetic stability as a single micelle template, MSVs can also be synthesized at low temperatures. However, the above work is limited by the synthesis system, the particle size of the synthesized product is large, and it is often accompanied by agglomeration.
[0005] Nonionic surfactants have larger molecular weights, and using them as templates can synthesize MSVs with larger pore sizes and higher thermal stability. Using Triton X-100 as a template, MSVs with a particle size of about 100 nm can be successfully synthesized; using block copolymers (EO 39 BO 47 EO 39 )B50-6600 was used as a template, and by adjusting the reaction conditions in a buffer solution, a unique raspberry-shaped MSV with a pore size of 15nm, a particle size of 80-150nm and a hierarchical structure was synthesized. However, the above research still did not solve the problems of product agglomeration and the formation of mixed phases.
[0006] In order to effectively solve the agglomeration problem, researchers often use organosilanes or other organic reagents such as mesitylene and triisopropylbenzene as additives to prepare MSVs. However, although this method can effectively solve the agglomeration problem and control the mesostructure of the final product, it still requires fine control of the molar ratio of each component or the reaction conditions.
[0007] Therefore, the single template method has the advantage of a simple synthesis system compared with the composite template method and the special template method. However, the pore size of MSVs prepared using cationic surfactants as a single template is small (<5nm), and researchers have not paid enough attention to the research on the preparation of large-pore MSVs using non-ionic surfactants as a single template, resulting in its very slow development. Summary of the invention
[0008] In order to solve the above-mentioned technical problems, the present invention provides a new method for preparing large-pore mesoporous silica nanovesicles (MSVs) with different morphologies and sizes.
[0009] The present invention provides a method for preparing large-pore mesoporous silica nanovesicles, and the preparation method specifically comprises the following steps:
[0010] S1, mixing water, a nonionic surfactant and a catalyst in proportion to obtain a mixed solution;
[0011] S2, heating the mixed solution to 30-41°C while stirring, adding the co-solvent, stirring for 15-20 minutes, adding the first part of the silicon source, stirring and reacting at a speed of 500-700 r / min for 1-4 hours, adding the second part of the silicon source, reacting at a speed of 500-700 r / min for 24 hours, and then transferring to an autoclave for hydrothermal reaction;
[0012] S3. After the hydrothermal reaction is completed, the mixture is cooled to room temperature to obtain a white precipitate. The white precipitate is centrifuged, washed, and dried to remove the surfactant to obtain large-pore mesoporous silica nanovesicles.
[0013] Compared with the prior art, the present invention uses a nonionic surfactant as a single template and proposes a simple and controllable synthesis system to prepare MSVs with good dispersion and no impurities, which is of great significance for the design and synthesis of nanovesicles, the development of inorganic carriers and microreactors.
[0014] In some embodiments, the molar ratio of the nonionic surfactant: the sum of the molar ratio of the first part of the silicon source and the second part of the silicon source: the co-solvent: the catalyst: the water is
[0015] 1:(65.93-79.07):(32.33-53.84):(563-1125):25814.
[0016] In some embodiments, in step S1, the nonionic surfactant is a polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, and the molecular weight is 5800.
[0017] In some embodiments, in step S1, the catalyst is boric acid, and is analytically pure.
[0018] Compared with the prior art, the present invention adopts boric acid as a catalyst to slow down the reaction rate of the synthesis system, which is beneficial to controlling the structure and morphology of the final product.
[0019] In some embodiments, in step S2, the parameters of the hydrothermal reaction are as follows: temperature is 100-140° C., and time is 24 h.
[0020] In some embodiments, in step S2, the co-solvent is benzyl alcohol, and the first part of the silicon source and the second part of the silicon source are both tetraethoxysilane.
[0021] Compared with the prior art, the present invention uses benzyl alcohol as an additive. The benzyl alcohol molecules can interact with the PPO chains of the P123 molecules to increase the V L The value of V H / V L The ratio of is beneficial to reduce the interface curvature of micelles and promote the formation of vesicle structure; in addition, the weak acid synthesis conditions are beneficial to slow down the hydrolysis and condensation rate of silicon species.
[0022] Compared with the prior art, the large-pore MSV-type mesoporous silica of the present invention uses a non-ionic surfactant as a template, benzyl alcohol as a co-solvent, boric acid as a catalyst, and tetraethoxysilane (TEOS) as a silicon source to prepare MSVs-type mesoporous silica. During the preparation process of the method of the present invention, due to the use of a spacing method, the -Si-OCH2CH3 group in the synthesis system is increased, which effectively slows down the hydrolysis rate of TEOS and is beneficial to the phase transition process.
[0023] In some embodiments, in step S2, the mass ratio of the first part of the silicon source to the second part of the silicon source is 4:1, and the mass ratio of the first part of the silicon source to the non-ionic surfactant is (1.18-2.96):1.
[0024] In some embodiments, in step S3, the surfactant is removed by calcination, and the parameters of the calcination method are as follows: temperature of 450-600°C, calcination time of 3-5h, and heating rate of 1-2°C / min.
[0025] The second object of the present invention is to provide a large-pore mesoporous silica nanovesicle prepared by any of the above-mentioned preparation methods.
[0026] In some embodiments, the large-pore mesoporous silica nanovesicles have a first-order pore size of 9-18 nm, a second-order pore size of 52-59 nm, a cavity size of 54-112 nm, and a specific surface area of 384-789 m 2 ·g -1 , pore volume is 0.86-1.68cm 3 ·g -1 , particle size is 96-140nm. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Performance test diagram of the large-pore mesoporous silica nanovesicles prepared in Example 1: SEM Figure 1 (a), TEM image Figure 1 (b), Figure 1 (c) is the nitrogen adsorption-desorption isotherm. Figure 1 (d) is the pore size distribution curve;
[0028] Figure 2 Performance test diagram of the large-pore mesoporous silica nanovesicles prepared in Example 2: SEM Figure 2 (a,b), Figure 2 (c) is the nitrogen adsorption-desorption isotherm. Figure 2 (d) is the pore size distribution curve;
[0029] Figure 3 Performance test diagram of the large-pore mesoporous silica nanovesicles prepared in Example 3: SEM Figure 3 (a,b), Figure 3 (c) is the nitrogen adsorption-desorption isotherm. Figure 3 (d) is the pore size distribution curve;
[0030] Figure 4 Performance test diagram of the large-pore mesoporous silica nanovesicles prepared in Example 4: SEM Figure 4 (a,b), Figure 4 (c) is the nitrogen adsorption-desorption isotherm. Figure 4 (d) is the pore size distribution curve;
[0031] Figure 5 Performance test diagram of the large-pore mesoporous silica nanovesicles prepared in Example 5: SEM Figure 5 (a,b), Figure 5 (c) is the nitrogen adsorption-desorption isotherm. Figure 5 (d) is the pore size distribution curve;
[0032] Figure 6 Performance test diagram of the large-pore mesoporous silica nanovesicles prepared in Example 6: SEM Figure 6 (a,b), Figure 6 (c) is the nitrogen adsorption-desorption isotherm. Figure 6 (d) is the pore size distribution curve;
[0033] Figure 7 Performance test diagram of the large-pore mesoporous silica nanovesicles prepared in Example 7: SEM Figure 7 (a,b), Figure 7 (c) is the nitrogen adsorption-desorption isotherm. Figure 7 (d) is the pore size distribution curve;
[0034] Figure 8 The performance test diagram of the large-pore mesoporous silica nanovesicles prepared in Comparative Example 1: SEM image as shown Figure 8 As shown in (a), Figure 8 (b) is the TEM image. DETAILED DESCRIPTION
[0035] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. It should be noted that the following embodiments are only used to illustrate the implementation method and typical parameters of the present invention, and are not used to limit the parameter range described in the present invention. Reasonable changes derived therefrom are still within the scope of protection of the claims of the present invention.
[0036] It should be noted that the endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.
[0037] Unless otherwise defined, all terms, symbols and other scientific terms used herein are intended to have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. In some cases, terms with conventionally understood meanings are defined herein for the purpose of clarification or ease of reference, and such definitions herein should not be construed as indicating significant differences from conventional understandings in the art. The technical methods described or cited herein are generally well understood by those skilled in the art and are adopted by conventional methods. Unless otherwise stated, the use of commercially available kits, reagents and instruments is carried out in accordance with the protocols and parameters given by the manufacturer.
[0038] The technical effects of the present invention are described below in conjunction with specific embodiments.
[0039] It should be noted that in the embodiments of the present invention, the raw materials used are:
[0040] Triblock nonionic surfactant P123, analytical grade, Sigma-Aldrich;
[0041] Benzyl alcohol analytical grade, Sigma-Aldrich;
[0042] Tetraethoxysilane (TEOS) relative density 0.93g93S -3 , analytical grade, Sinopharm Chemical Reagent Co., Ltd.;
[0043] Boric acid, analytical grade, was purchased from Sinopharm Chemical Reagent Co., Ltd.
[0044] Example 1
[0045] The present embodiment provides a large-pore mesoporous silica nanovesicle, which is prepared by the following preparation method: according to the molar ratio of non-ionic surfactant: silicon source: co-solvent: catalyst: water = 1: 65.93: 43.07: 750: 25814, 5g (10wt%) P123 aqueous solution, 35.5g deionized water and 4g H3BO3 are stirred evenly in a 33.5°C water bath, 0.4g benzyl alcohol is added, and after stirring for 15min, 1.18g tetraethoxysilane is added and stirred for 4h, followed by 0.3g tetraethoxysilane and stirring for 24h. After the reaction is completed, the mixed solution is transferred to a high-pressure reactor and hydrothermal at 100°C for 24h. Finally, it is centrifugally washed with deionized water, dried and calcined. The calcination conditions are: 550°C, 4h, and the heating rate is 1.5°C·min -1 The obtained MSVs mesoporous silica was named 8-4h-2@33.5-4B-0.4Bz-100HT.
[0046] Embodiment 2:
[0047] The present embodiment provides a large-pore mesoporous silica nanovesicle, which is prepared by the following preparation method: according to the ratio of non-ionic surfactant: silicon source: co-solvent: catalyst: water = 1:65.93:43.07:563:25814, 5g (10wt%) P123 aqueous solution, 35.5g deionized water and 3g H3BO3 are stirred evenly in a water bath at 33.5°C, 0.4g benzyl alcohol is added, and after stirring for 15min, 1.18g tetraethoxysilane is added and stirred for 4h, and then 0.3g tetraethoxysilane is added and stirred for 24h. After the reaction is completed, the mixed solution is transferred to a high-pressure reactor and hydroheated at 100°C for 24h. Finally, it is washed by centrifugation with deionized water, dried and calcined. The calcination conditions are: 550°C, 4h, and the heating rate is 1.5°C·min -1 The obtained MSVs mesoporous silica was named 8-4h-2@33.5-3B-0.4Bz-100HT.
[0048] Example 3
[0049] The present embodiment provides a large-pore mesoporous silica nanovesicle, which is prepared by the following preparation method: according to the ratio of non-ionic surfactant: silicon source: co-solvent: catalyst: water = 1:65.93:32.33:750:25814, 5g (10wt%) P123 aqueous solution, 35.5g deionized water and 4g H3BO3 are stirred evenly in a water bath at 33.5°C, 0.3g benzyl alcohol is added, and after stirring for 15min, 1.18g tetraethoxysilane is added and stirred for 4h, and then 0.3g tetraethoxysilane is added and stirred for 24h. After the reaction is completed, the mixed solution is transferred to a high-pressure reactor and hydroheated at 100°C for 24h. Finally, it is washed by centrifugation with deionized water, dried and calcined. The calcination conditions are: 550°C, 4h, and the heating rate is 1.5°C·min -1 The obtained MSVs mesoporous silica was named 8-4h-2@33.5-4B-0.3Bz-100HT.
[0050] Example 4
[0051] The present embodiment provides a large-pore mesoporous silica nanovesicle, which is prepared by the following preparation method: according to the ratio of non-ionic surfactant: silicon source: co-solvent: catalyst: water = 1: 65.93: 43.07: 750: 25814, 5g (10wt%) P123 aqueous solution, 35.5g deionized water and 4g H3BO3 are stirred evenly in a water bath at 33.5°C, 0.4g benzyl alcohol is added, and after stirring for 15min, 1.03g tetraethoxysilane is added and stirred for 4h, and then 0.45g tetraethoxysilane is added and stirred for 24h. After the reaction is completed, the mixed solution is transferred to a high-pressure reactor and hydroheated at 100°C for 24h. Finally, it is washed by centrifugation with deionized water, dried and calcined. The calcination conditions are: 550°C, 4h, and the heating rate is 1.5°C·min -1 The obtained MSVs mesoporous silica was named 7-4h-3@33.5-4B-0.4Bz-100HT.
[0052] Example 5
[0053] The present embodiment provides a large-pore mesoporous silica nanovesicle, which is prepared by the following preparation method: according to the ratio of non-ionic surfactant: silicon source: co-solvent: catalyst: water = 1: 65.93: 43.07: 750: 25814, 5g (10wt%) P123 aqueous solution, 35.5g deionized water and 4g H3BO3 are stirred evenly in a water bath at 33.5°C, 0.4g benzyl alcohol is added, and after stirring for 15min, 1.18g tetraethoxysilane is added and stirred for 1h, and then 0.30g tetraethoxysilane is added and stirred for 24h. After the reaction is completed, the mixed solution is transferred to a high-pressure reactor and hydroheated at 100°C for 24h. Finally, it is washed by centrifugation with deionized water, dried and calcined. The calcination conditions are: 550°C, 4h, and the heating rate is 1.5°C·min -1 The obtained MSVs mesoporous silica was named 8-1h-2@33.5-4B-0.4Bz-100HT.
[0054] Example 6
[0055] This embodiment provides a large-pore mesoporous silica nanovesicle, which is prepared by the following preparation method: according to non-ionic surfactant: silicon source: co-solvent: catalyst: water = 1: 65.93: 43.07: 750: 25814, 5g (10wt%) P123 aqueous solution, 35.5g deionized water and 4g H3BO3 are stirred evenly in a water bath at 28.5°C, 0.4g benzyl alcohol is added, and after stirring for 15min, 1.18g tetraethoxysilane is added and stirred for 4h, followed by 0.30g tetraethoxysilane and stirring for 24h. After the reaction is completed, the mixed solution is transferred to a high-pressure reactor, hydrothermal at 100°C for 24h, and finally, centrifuged with deionized water, washed, dried and calcined. Calcination conditions: 550°C, 4h, heating rate of 1.5°C·min -1 The obtained MSVs mesoporous silica was named 8-4h-2@28.5-4B-0.4Bz-100HT.
[0056] Example 7
[0057] The present embodiment provides a large-pore mesoporous silica nanovesicle, which is prepared by the following preparation method: according to the ratio of non-ionic surfactant: silicon source: co-solvent: catalyst: water = 1: 65.93: 43.07: 750: 25814, 5g (10wt%) P123 aqueous solution, 35.5g deionized water and 4g H3BO3 are stirred evenly in a 33.5°C water bath, 0.4g benzyl alcohol is added, and after stirring for 15min, 1.18g tetraethoxysilane is added and stirred for 4h, and then 0.30g tetraethoxysilane is added and stirred for 24h. After the reaction is completed, the mixed solution is transferred to a high-pressure reactor and hydroheated at 140°C for 24h. Finally, it is washed by centrifugation with deionized water, dried and calcined. The calcination conditions are: 550°C, 4h, and the heating rate is 1.5°C·min -1 The obtained MSVs mesoporous silica was named 8-4h-2@33.5-4B-0.4Bz-140HT.
[0058] Comparative Example 1
[0059] The present comparative example provides a large-pore mesoporous silica nanovesicle, which is prepared by the following preparation method: according to the ratio of silicon source: non-ionic surfactant: co-solvent: catalyst: water = 1: 0.338: 0.270: 2.70: 23.986, 5g (10wt%) P123 aqueous solution, 35.5g deionized water and 4g H3BO3 are stirred evenly in a 33.5°C water bath, 0.4g benzyl alcohol is added, and after stirring for 15min, 1.48g TEOS is added, and the mixed solution is stirred at 33.5°C for 24h. After the reaction is completed, the mixed solution is transferred to a high-pressure reactor and hydroheated at 100°C for 24h. Finally, it is washed by centrifugation with deionized water, dried and calcined. The calcination conditions are: 550°C, 4h, and the heating rate is 1.5°C·min -1 The obtained MSVs mesoporous silica was named 10-0@33.5-4B-0.4Bz-100HT.
[0060] The performance of the large-pore mesoporous silica nanovesicles prepared in Examples 1-7 and Comparative Example 1 was tested. The test results are as follows: Figure 1-Figure 8 As shown, Figure 1 Performance test diagram of the large-pore mesoporous silica nanovesicles prepared in Example 1: SEM Figure 1 (a), TEM image Figure 1 (b), Figure 1 (c) is the nitrogen adsorption-desorption isotherm. Figure 1 (d) is the pore size distribution curve, from Figure 1It can be seen that the MSVs mesoporous silica prepared in Example 1 has a good spherical structure, a particle size of 119 nm, and a large pore size. The first-order pore size is 9 nm, the second-order pore size is 54 nm, and the specific surface area is 621 m 2 ·g -1 , pore volume is 1.00 cm 3 ·g -1 The hysteresis loop shape of the nitrogen adsorption-desorption isotherm is a typical H3 type, which can be judged to have a vesicle structure.
[0061] Figure 2 Performance test diagram of the large-pore mesoporous silica nanovesicles prepared in Example 2: SEM Figure 2 (a,b), Figure 2 (c) is the nitrogen adsorption-desorption isotherm. Figure 2 (d) is the pore size distribution curve, from Figure 2 It can be seen that the MSVs mesoporous silica prepared in Example 2 has a good spherical structure, a particle size of 111 nm, and a large pore size. The first-order pore size is 10 nm, the second-order pore size is 59 nm, and the specific surface area is 789 m 2 ·g -1 , the pore volume is 1.27 cm 3 ·g -1 The hysteresis loop shape of the nitrogen adsorption-desorption isotherm is a typical H3 type, which can be judged to have a vesicle structure.
[0062] Figure 3 Performance test diagram of the large-pore mesoporous silica nanovesicles prepared in Example 3: SEM Figure 3 (a,b), Figure 3 (c) is the nitrogen adsorption-desorption isotherm. Figure 3 (d) is the pore size distribution curve, from Figure 3 It can be seen that the MSVs prepared in Example 3 contain a large amount of two-dimensional hexagonal heterophase and have a large pore size of 9 nm and a specific surface area of 791 m 2 ·g -1 , the pore volume is 1.14 cm 3 ·g -1 The hysteresis loop shape of the nitrogen adsorption-desorption isotherm is a typical H3 type, which can be judged to have a vesicle structure.
[0063] Figure 4 Performance test diagram of the large-pore mesoporous silica nanovesicles prepared in Example 4: SEM Figure 4 (a,b), Figure 4 (c) is the nitrogen adsorption-desorption isotherm. Figure 4 (d) is the pore size distribution curve, from Figure 4It can be seen that the MSVs mesoporous silica prepared in Example 4 has a good spherical structure, a particle size of 103 nm, and a relatively large pore size, with a first-order pore size of 9 nm, a second-order pore size of 54 nm, and a specific surface area of 580 m 2 ·g -1 , the pore volume is 0.94 cm 3 ·g -1 The hysteresis loop shape of the nitrogen adsorption-desorption isotherm is a typical H3 type, which can be judged to have a vesicle structure.
[0064] Figure 5 Performance test diagram of the large-pore mesoporous silica nanovesicles prepared in Example 5: SEM Figure 5 (a,b), Figure 5 (c) is the nitrogen adsorption-desorption isotherm. Figure 5 (d) is the pore size distribution curve, from Figure 5 It can be seen that the MSVs mesoporous silica prepared in Example 5 has a good spherical structure, a particle size of 140 nm, and a large pore size, the first-order pore size is 9 nm, the second-order pore size is 58 nm, and the specific surface area is 699 m 2 ·g -1 , the pore volume is 1.07 cm 3 ·g -1 The hysteresis loop shape of the nitrogen adsorption-desorption isotherm is a typical H3 type, which can be judged to have a vesicle structure.
[0065] Figure 6 Performance test diagram of the large-pore mesoporous silica nanovesicles prepared in Example 6: SEM Figure 6 (a,b), Figure 6 (c) is the nitrogen adsorption-desorption isotherm. Figure 6 (d) is the pore size distribution curve, from Figure 6 It can be seen that the MSVs mesoporous silica prepared in Example 6 has a good spherical structure, but it is doped with a two-dimensional hexagonal phase and has a larger pore size of 13 nm and a specific surface area of 767 m 2 ·g -1 , the pore volume is 1.68 cm 3 ·g -1 The hysteresis loop shape of the nitrogen adsorption-desorption isotherm is a typical H3 type, which can be judged to have a vesicle structure.
[0066] Figure 7 Performance test diagram of the large-pore mesoporous silica nanovesicles prepared in Example 7: SEM Figure 7 (a,b), Figure 7 (c) is the nitrogen adsorption-desorption isotherm. Figure 7 (d) is the pore size distribution curve, from Figure 7 It can be seen that the MSVs mesoporous silica prepared in Example 7 has a better spherical structure, a larger cavity size, better sphericity, and a larger pore size. The first-order pore size is 18nm, the first-order pore size is 58nm, and the specific surface area is 384m 2 ·g -1 , the pore volume is 1.34 cm 3 ·g -1 The hysteresis loop shape of the nitrogen adsorption-desorption isotherm is a typical H3 type, which can be judged to have a vesicle structure.
[0067] Figure 8 The performance test diagram of the large-pore mesoporous silica nanovesicles prepared in Comparative Example 1: SEM image as shown Figure 8 As shown in (a), Figure 8 (b) is a TEM image. Figure 8 It can be seen that mesoporous silica is a mixture of vesicles and two-dimensional hexagonal phases. Due to the one-time addition of too much silicon source, the TEOS reaction rate increases, and the addition of benzyl alcohol is not enough to change the micelle curvature, thereby promoting the formation of a two-dimensional phase.
[0068] Although the disclosure is disclosed as above, the protection scope of the disclosure is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the disclosure, and these changes and modifications will fall within the protection scope of the present invention.
Claims
1. A method for preparing large-pore mesoporous silica nanovesicles, characterized in that: The preparation method specifically comprises the following steps: S1, mixing water, a nonionic surfactant and a catalyst in proportion to obtain a mixed solution; S2, heating the mixed solution to 30-41°C while stirring, adding the co-solvent, stirring for 15-20 minutes, adding the first part of the silicon source, stirring and reacting at a speed of 500-700 r / min for 1-4 hours, adding the second part of the silicon source, reacting at a speed of 500-700 r / min for 24 hours, and then transferring to an autoclave for hydrothermal reaction; S3. After the hydrothermal reaction is completed, the mixture is cooled to room temperature to obtain a white precipitate. The white precipitate is centrifuged, washed, and dried to remove the surfactant to obtain large-pore mesoporous silica nanovesicles.
2. The method for preparing large-pore mesoporous silica nanovesicles according to claim 1, characterized in that: In terms of molar ratio, the sum of the molar ratios of nonionic surfactant: the first part of the silicon source and the second part of the silicon source: co-solvent: catalyst: water is 1:(65.93-79.07):(32.33-53.84):(563-1125):25814.
3. The method for preparing large-pore mesoporous silica nanovesicles according to claim 1, characterized in that: In the step S1, the nonionic surfactant is a polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, and the molecular weight is 5800.
4. The method for preparing large-pore mesoporous silica nanovesicles according to claim 1, characterized in that: In step S1, the catalyst is boric acid, and is analytically pure.
5. The method for preparing large-pore mesoporous silica nanovesicles according to claim 1, characterized in that: In step S2, the parameters of the hydrothermal reaction are as follows: temperature is 100-140° C., and time is 24 hours.
6. The method for preparing large-diameter mesoporous silica nanovesicles according to claim 1, characterized in that: In the step S2, the co-solvent is benzyl alcohol, and the first part of the silicon source and the second part of the silicon source are both tetraethoxysilane.
7. The method for preparing large-diameter mesoporous silica nanovesicles according to claim 1, characterized in that: In step S2, the mass ratio of the first part of the silicon source to the second part of the silicon source is 4:1, and the mass ratio of the first part of the silicon source to the non-ionic surfactant is (1.18-2.96):
1.
8. The method for preparing large-pore mesoporous silica nanovesicles according to claim 1, characterized in that: In step S3, the surfactant is removed by calcination, and the parameters of the calcination method are as follows: temperature is 450-600° C., calcination time is 3-5 hours, and heating rate is 1-2° C. / min.
9. A large-pore mesoporous silica nanovesicle, characterized in that: The method is prepared by any one of claims 1 to 8.
10. The macroporous mesoporous silica nanovesicle according to claim 9, characterized in that: The large-aperture mesoporous silica nanovesicles have a first-order pore size of 9-18 nm, a second-order pore size of 52-59 nm, a cavity size of 54-112 nm, and a specific surface area of 384-789 m 2 ·g -1 , pore volume is 0.86-1.68cm 3 ·g -1 , particle size is 96-140nm.
